Pengaruh Kebijakan Dividen, Sustainability Report Terhadap Nilai Perusahaan (Studi Empiris Pada Perusahaan BUMN Go Public yang terdaftar di Bursa Efek Indonesia Periode 2010-2016) - Indah Lia Puspita; Putri Dhia Fairuz (Jurnal Riset Akuntansi dan Manajemen Malahayati, 2018)
This study aims to analyze the Influence of Policy Dividen, Sustainability Report AgainstValue Company Bumn Go Public Company Year 2010-2016 This study uses 42 samples from companyBUMN Go Public Year 2010-2016. The sample is selected using the puposive sampling method. Thetype of data used is secondary data. Data analysis using descriptive statistics, classical assumptiontest, multiple linear regression test.The results of this study partially or simultaneously do not have theeffect of dividend policy, sustainability report against corporate value.